STUDI LITERASI TENTANG STRATEGI PENGEMBANGAN BISNIS HORTIKULTURA - Santoso, Wahyu Imam; Ariq Surya Antoro, Muhammad; Labib, Sayid (Universitas Muhammadiyah Semarang, 2024)
This article aims to discuss horticulture business development strategies in Indonesia, which has high economic potential and plays an important role in providing food and innovative industries. The research uses a bibliometric approach to analyse trends and patterns in horticulture business research. Some of the suggested strategies include leading statistical surveys, choosing the right plant products, creating intensive marketing strategies, and co-operating with other groups. Public authorities also need to support the development of horticulture businesses through policies that favour farmers and innovation. Research or articles that discuss horticulture businesses have continued to increase over the past ten years. This shows that research on horticultural business development is still very interesting to do.